2006
DOI: 10.1038/ng1830
|View full text |Cite
|
Sign up to set email alerts
|

The multidrug-resistant human pathogen Clostridium difficile has a highly mobile, mosaic genome

Abstract: We determined the complete genome sequence of Clostridium difficile strain 630, a virulent and multidrug-resistant strain. Our analysis indicates that a large proportion (11%) of the genome consists of mobile genetic elements, mainly in the form of conjugative transposons. These mobile elements are putatively responsible for the acquisition by C. difficile of an extensive array of genes involved in antimicrobial resistance, virulence, host interaction and the production of surface structures. The metabolic cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
950
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 819 publications
(996 citation statements)
references
References 50 publications
40
950
1
5
Order By: Relevance
“…In the first C. difficile genome to be sequenced, str. 630 (RT 012), mobile elements accounted for ~10% of the genome and included a plasmid, prophages, transposons, IStrons, genomic islands, CRISPRs and a skin element (Sebaihia et al, 2006). This has remained consistent in the annotated genomes of other strains published since, including M120 (clade 5), and R20291 (clade 2) (He et al, 2010;Stabler et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 71%
See 2 more Smart Citations
“…In the first C. difficile genome to be sequenced, str. 630 (RT 012), mobile elements accounted for ~10% of the genome and included a plasmid, prophages, transposons, IStrons, genomic islands, CRISPRs and a skin element (Sebaihia et al, 2006). This has remained consistent in the annotated genomes of other strains published since, including M120 (clade 5), and R20291 (clade 2) (He et al, 2010;Stabler et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 71%
“…630 contained seven conjugative transposons (CTn1-CTn7), and one mobilisable transposon Tn5398 (Sebaihia et al, 2006). The conjugative transposons are divided into two main families based on their conjugation modules, the Tn916 family, and the Tn1549 family (Sebaihia et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene transfer was suggested to be mediated by megaplasmids, based on the identification of 10 such plasmids carrying CRISPR arrays 22,33 . Interestingly, a CRISPR array was also found within a Clostridium difficile prophage, and it was suggested that the phage uses the CRISPR to limit dispersal of competing phages 34 .…”
Section: Evolution Of Crispr Systemsmentioning
confidence: 99%
“…Conversely, in tetracycline-resistant, erm(TR)-positive S. pyogenes isolates, a completely different genetic element, in which erm(TR) is linked to the tet(O) gene, has recently been characterized (3). This new structure, designated ICESp2905 (ϳ66 kb), results from two separate fragments, one containing erm(TR) and one containing tet(O), being integrated into a scaffold of clostridial origin (a putative ICE from Clostridium difficile strain 630 [16]). Remarkably, both ICESp1108 and ICESp2905 are integrated in the chromosome at the 3= end of the conserved RNA uracil methyltransferase (rum) gene, which is an integration hot spot for several mobile streptococcal elements (3).…”
mentioning
confidence: 99%